2021
DOI: 10.3390/life11111210
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing CRISPR-Cas to Combat COVID-19: From Diagnostics to Therapeutics

Abstract: The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains a global threat with an ever-increasing death toll even after a year on. Hence, the rapid identification of infected individuals with diagnostic tests continues to be crucial in the on-going effort to combat the spread of COVID-19. Viral nucleic acid detection via real-time reverse transcription polymerase chain reaction (rRT-PCR) or sequencing is regarded as the gold standard for COVID-19 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…In combination with the isothermal amplification technique, several research groups have reported the advancement of diagnostic tool designs originating from the CRISPR-Cas system, and have developed various assays based on Cas12 and Cas13 to detect SARS-CoV-2. 2,5,6 Saliva samples were used as an attractive choice owing to their non-invasive, repeatable, and simple collection procedure. Moreover, during the first week of infection, it has been reported that more viral particles could be retrieved from saliva compared to NP swab samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with the isothermal amplification technique, several research groups have reported the advancement of diagnostic tool designs originating from the CRISPR-Cas system, and have developed various assays based on Cas12 and Cas13 to detect SARS-CoV-2. 2,5,6 Saliva samples were used as an attractive choice owing to their non-invasive, repeatable, and simple collection procedure. Moreover, during the first week of infection, it has been reported that more viral particles could be retrieved from saliva compared to NP swab samples.…”
Section: Discussionmentioning
confidence: 99%
“…4 Meanwhile, the use of the CRISPR (clustered regularly interspaced short palindromic repeats)-Cas system in molecular diagnostics has increased exponentially. 2,5,6 Several CRISPR/Cas-based assays have been developed because the system offers highly specific nucleic acid detection. In our previous studies, we reported the detection of SARS-CoV-2 RNA based on CRISPR-Cas12a.…”
Section: Impact Statementmentioning
confidence: 99%
“…Our research was focused on finding optimal target sequences in the SARS-CoV-2 RNA genome for a therapeutic attack, but this work may also have relevance for viral diagnostics based on the CRISPR-Cas technology, in particular, the interaction between the crRNA and the viral RNA genome [113][114][115]. It seems fair to extend our current finding of optimal therapeutic target sites to candidate target sequences for viral diagnostics.…”
Section: Future Perspectivementioning
confidence: 99%
“…Presently, a range of nucleic acid amplification tests (NAATs) have been granted emergency use authorization (EUA) status by the US Food and Drug Administration (FDA). These include non-isothermal- and isothermal-based amplification technologies with various amplicon detection methods being employed such as fluorometric, colorimetric, electrochemical, magnetic resonance, clustered regularly interspaced short palindromic repeats/Cas systems, matrix-assisted laser desorption ionization time-of-flight and sequencing [ 8 , 9 ]. However, the technical intricacies and sophisticated instrument requirements of FDA-EUA nucleic acid tests confine most of them to Clinical Laboratory Improvement Amendments (CLIA)-certified, high-complexity laboratories.…”
Section: Introductionmentioning
confidence: 99%